ICT-enabled supply chain integration capabilities and firms' financial performance: an empirical study of Tanzania's manufacturing SMEs - Veneranda Rutainurwa; Beny Mwenda; Baraka Israel (Cogent Business & Management, 2024)
The spectacular advancement in information and communication technology (ICT) has shaped the way firms conduct their business, interact and communicate with customers and suppliers along their supply chains (SC). Yet, there exists limited knowledge of how investing in ICT can be leveraged to help firms streamline SC integration and achieve sustainable financial performance (FPF). Drawing on dynamic capability theory, this research delineates the dimensions of internal SC integration (ISI) and external SC integration (ESI) as potential mediators of the relationship between ICT capabilities and a firm's FPF. A simple random sampling approach and cross-sectional questionnaire survey were used for data collection from 274 manufacturing SMEs in the Mbeya region, Tanzania. Subsequently, the collected data was analysed using Hayes PROCESS macro model 4 to test the study hypotheses. Empirical results indicate an insignificant direct effect of ICT capabilities on a firm's FPF. However, ICT capabilities significantly and positively affect both ISI and ESI, which in turn play critical mediating roles, positively impacting the firm's FPF. Essentially, the findings imply that the pathway from ICT capabilities to FPF predominantly transpires through enhanced ISI and ESI. As such, the study underscores the importance for SME managers to invest in ICT capabilities and harness such capabilities to strengthen ISI and ESI as the strategic intermediaries that translate ICT investments into tangible financial outcomes. The study contributes to the existing few empirical studies that establish the potential mediating effect of SC integration in the link between ICT capabilities and a firm's FPF.
Keywords: 650; ICT capabilities; internal SC integration; external SC integration; financial performance; manufacturing smes